Pemanfaatan Gracillaria sp. sebagai Agen Biofilter pada Udang Vaname (Litopenaeus vannamei) yang Dibudidayakan di Laboratorium - Maimunah, Yunita; Kurniaty, Vida; Sanoesi, Ellana (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
Shrimp feed contains nitrogen and phosphorus, which are essential nutrients for shrimp growth. However, not all of the feed is consumed by the shrimp, and some of it becomes waste that accumulates in the water. There are various methods to reduce ammonia and phosphate, one of it is by bioremediation. One promising biofilter material for shrimp farming is Gracillaria sp that can absorb ammonia and phosphate from the water. Gracillaria sp. can also produce agar, a valuable substance for various industries. This research uses Gracillaria sp with different weights for bioremediation of vannamei shrimp farming effluent. Method used was experimental in Laboratory with 4 treatments, there are K: Gracillaria sp weight of 100 grams (control without shrimp), A : Gracillaria sp weight of 1 300 grams, B: Gracillaria sp. weight of of 450 grams and C: Gracillaria sp weight of 600 grams. The results showed that Gracillaria sp. can effectively reduce the levels of ammonia and phosphate in water, with biofilter efficiency reaching up to 92% for phosphate and 64% for ammonia. The higher the weight of Gracillaria sp. used in the biofilter, the more efficient it was at removing ammonia and phosphate. Additionally, Gracillaria sp. can also produce agar, a valuable substance for various industries.